Delay model of multicast protocols co‐existing with legacy unicast in IEEE 802.11 wireless local area network. Issue 9 (26th June 2017) - Kim, Igor; Park, Seungkeun
Abstract : Reliable and QoS‐aware multimedia delivery is one of the most important requirements to satisfy end user needs. IEEE 802.11 networks have become one of the most popular Internet access methods owing to their low‐cost and fast connection speed. Multicasting is a transmission technique that can significantly increase network efficiency through the simultaneous delivery of the same multimedia content to multiple multicast group members. IEEE 802.11 describes several multicast protocols targeted to increase the robustness of audio and video delivery. Some researchers have investigated the performance of such multicast protocols in terms of their achievable throughput. However, for a better understanding of the suitability of the protocols for a QoS‐aware multimedia transmission, an in‐depth analysis of the achievable delay is needed. This study provides a detailed delay analysis and describes analytical models for estimating the average achievable delay of IEEE 802.11 multicast protocols co‐existing with legacy stations. The proposed analytical models are compared against simulation results under various conditions and parameter configurations. The simulation results validate the accuracy of the proposed models.